Profit And Loss Sharing Under Syari’ah Contract At BTN Syari’ah Bank Pekanbaru, Indonesia - Arben, Ali; mirwati, Yulia; warman, Kurnia; Fendri, Azmi; Rusli, Devi (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia the concept of Islamic Bank was introduced with the establishment of PT. Bank Muamalat Indonesia, Tbk (BMI) in 1991 and operated a year later. The burgeoning BMI was initiated by the Indonesian Ulema Council supported by Muslim entrepreneurs and Muslim scholars. At present the development of Islamic banking is not only in Bank services but also adds other sectors such as Sharia Insurance, Sharia Bonds, Sharia Mutual Funds and other products. However, the incessant and bright spots of Islamic banking turned out to be not followed by sufficient regulations to back up the formal juridical of Islamic operations, so that currently the rules that are used only take advantage of existing legal gaps, especially the gaps given in the Law. No. 10 of 1998 concerning Banking. Also, due to the lack of deregulation support at the level of the Law, currently operational is only regulated by Bank Indonesia Regulation (PBI) as an operational basis for Islamic banks. This paper seeks to answer the following questions: What are the forms of financing facilities and implementation of the Syari’ah agreement at Bank BTN Syari’ah Pekanbaru? And what is the principle of profit-sharing and risk sharing (Profit and Loss Sharing) between the parties of the Pekanbaru Syari’ah Savings Bank and the Debtor?